Moldova - After the Global Crisis : Promoting Competitiveness and Shared Growth - World Bank (World Bank, 2012)
This report argues that in the future Moldova will need to develop a second engine of growth from exports of goods and services. We argue that Moldova needs to resurrect agro-based exports, to raise their value by exporting to higher value markets, and develop service exports in order to provide job opportunities for underemployed tertiary graduates. To be successful in doing so, the government will need to implement deep fiscal and structural reforms to break the cycle, while taking advantage of productivity gains. Much needs fixing, and Moldova's public sector does not have the capacity to fix it all. Moldova's leaders need to reach consensus on a comprehensive and sequenced growth and poverty reduction strategy. This report sketches out what such a strategy should contain. The author suggests that geography and the Government's policy stance fundamentally shape Moldova's economic growth potential and the path and priorities that a growth strategy should follow. Government needs to accelerate reforms so that the country can emerge from the global crisis-induced recession with faster and less vulnerable growth. Business as usual will not suffice. The world's capital markets have become tighter, foreign investors more demanding, and export markets more competitive. In April 2009, Moldova's youth indicated that that they can no longer stand aside and watch Moldova fall behind, they have called for a politics of aspiration, and they will demand economic policies consistent with these aspirations.